MODERN APPROACHES AND OPPORTUNITIES FOR THE EVALUATION OF CARDIOVASCULAR SYSTEM IN CHILDHOOD SPORTS - L. A. Balykova; S. A. Ivyansky; А. А. Shirokova; N. V. Shchyokina; N. А. Kalabkin (Кардиоваскулярная терапия и профилактика)
The article focuses on the modern approaches to evaluation of stress- induced changes in cardiovascular system in young people, regularly participating in sports. The problem of early and achievable diagnostics is highlighted, as by the experience of some abroad experts. Based upon literary data on the risk stratification of life-threatening conditions development in adult athletes and upon our own clinical experience we propose the original approach to diagnostics of desadaptational changes in cardiovascular system of adolescent sportsmen. The fundamentals for more relevant confirmation of stress-induced cardiomyopathy are provided, including non-proved sportsmen withdraw.